Chronic Subdural Hematoma : A Review - Gupta, Sajag Kumar (Nepal Journal of Neuroscience, 2022)
Chronic subdural haematoma (CSDH) is an encapsulated collection of old blood between the dura mater and arachnoid caused by tear of bridging veins. Chronic subdural haematoma is considered when the blood is more than three weeks old. It is fairly common disease, especially in the elderly with incidence ranging 1.72 to 7. 35 per 100,000 population with male predominance. Elderly population is associated co- morbidities that can impact on immediate postoperative outcome and overall survival. Although history of trivial trauma is present in majority of cases but some cases may be secondary to coagulation defect, intracranial hypotension, and use of anticoagulant and antiplatelet agents. It commonly presents with headaches, confusion, drowsiness, vomiting, and seizures. On examination, patient have various neurological deficits including a low Glasgow coma scale, hemiparesis/hemiplegia, ocular palsy, and other deficits are seen .Diagnosis is usually confirmed by NCCT scan head however MRI are indicated for better visualisation of multiloculated intrahaematoma membranes.Management of this condition is mostly surgery but some patients have also been managed conservatively  with steroids. Steroids have been  used in patient who have minor headache and also used in patients who are unfit for surgery.